2021
DOI: 10.1029/2020rs007244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atmospheric Refractivity Estimation Methods and Their Influence on Radar Propagation Predictions

Abstract: Environmental predictions in the marine atmospheric surface layer (MASL) are imperative to optimize X‐band radar system performance in marine environments. Evaporation ducts (ED) lead to anomalous propagation where characterization of EDs in the MASL occurs primarily through two methods: in‐situ measurements and numerical modeling. This study investigates the differences in co‐located and synchronous refractivity estimations from the CASPER‐East campaign. Propagation predictions are generated for refractive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…which are known to have significant effects on PL (Cherrett, 2015;Hitney & Vieth, 1990;Pastore et al, 2021). Neutral/stable regimes generally correspond to higher duct heights from the inversion solution, which is consistent with previous studies showing EDH increases in stable environments (Cherrett, 2015;Zhang et al, 2017).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…which are known to have significant effects on PL (Cherrett, 2015;Hitney & Vieth, 1990;Pastore et al, 2021). Neutral/stable regimes generally correspond to higher duct heights from the inversion solution, which is consistent with previous studies showing EDH increases in stable environments (Cherrett, 2015;Zhang et al, 2017).…”
Section: Resultssupporting
confidence: 89%
“…The most striking differences occur with respect to the mixed layer slope (e.g., Figures 9A, 9I or 9L); however, it has been shown that differences in the mixed layer slope do not affect propagation as significantly as other refractive parameters in the near surface (Lentini & Hackett, 2015;Matsko & Hackett, 2019;Pastore et al, 2021;Penton & Hackett, 2018), resulting in a relative insensitivity of the GA optimization to this parameter. Much more important is the duct height and the shape below the duct height (Cherrett, 2015;Pastore et al, 2021). In many cases, EDHs from the inversions are similar to other estimates 1).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations